The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3357/asem.2231.2008
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol and Exercise Effects on Ankle Extensor Strength during 40 Days of Unloading

Abstract: The combined RE-albuterol treatment most likely evoked unloaded AEXT strength gains in women due to heightened myofibril sensitivity for Ca+2. Despite a drug/body mass covariate, gender-related differences should be interpreted with caution. Future work should compare absolute and relative beta2 agonist dosages on gender-related muscle mass and strength changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…There is also evidence that women may have greater benefits when using this combined intervention compared with men as evidenced by increased total work and power during exercise sessions. The difference has been hypothesized to occur because of enhanced myofibril sensitivity for calcium in women (Caruso et al 2008). Overall, by coupling this pharmacological agent with resistance exercise, multiple systems are targeted and potentially protected from the negative alterations associated with unloading.…”
Section: Exercise Countermeasuresmentioning
confidence: 99%
“…There is also evidence that women may have greater benefits when using this combined intervention compared with men as evidenced by increased total work and power during exercise sessions. The difference has been hypothesized to occur because of enhanced myofibril sensitivity for calcium in women (Caruso et al 2008). Overall, by coupling this pharmacological agent with resistance exercise, multiple systems are targeted and potentially protected from the negative alterations associated with unloading.…”
Section: Exercise Countermeasuresmentioning
confidence: 99%
“…Greater losses generally occur with longer flights, with the rate of strength loss exceeding that for muscle atrophy (7,16). The stimulus for in-flight knee extensor losses is a lack of mechanical loading (16).…”
Section: Introductionmentioning
confidence: 99%
“…The merits of FERG workouts were assessed in ambulatory and ground-based microgravity simulation models (7)(8)(9)(10). In addition, the FERG was examined for its utility in Earthbound applications, such as to abate musculoskeletal losses in the elderly (6).…”
Section: Introductionmentioning
confidence: 99%
“…Caruso et al. [201], however, presented a positive effect on performance by oral administration of salbutamol or albuterol [202]. Similarly, another study showed that a single oral dose of salbutamol increased isokinetic muscle strength and endurance performance in healthy male volunteers [203].…”
Section: Beta‐2 Adrenergic Agonistsmentioning
confidence: 99%
“…In humans, little evidence exists for increase in physical performance after inhalation of salbutamol [196,197], salmeterol [198], formoterol [199], or terbutaline [200]. Caruso et al [201], however, presented a positive effect on performance by oral administration of salbutamol or albuterol [202]. Similarly, another study showed that a single oral dose of salbutamol increased isokinetic muscle strength and endurance performance in healthy male volunteers [203].…”
Section: B E T a -2 A D R E N E R G I C A G O N I S T Smentioning
confidence: 99%